Dataset of dual RNA-sequencing of Phytophthora palmivora infecting coconut (Cocos nucifera L.) - K.P. Gangaraj; M.K. Rajesh (Data in Brief, 2020)
Phytophthora spp. is an oomycetes pathogen which causes serious damage to a wide range of crops. Bud rot disease of coconut palm, caused by P. palmivora, causes huge economic losses since it cannot be detected at an early stage. Utilizing dual RNA-sequencing (RNA-seq), we have simultaneously investigated the gene expression patterns in both, the infecting oomycete (P. palmivora) and infected host (coconut leaflets). Samples were collected at three time points viz., 12, 24 and 36 h, from both infected and uninfected (control) tissues and subjected to RNA-seq on an Illumina Hiseq™ 2500 sequencing platform. High quality reads obtained were subjected to mapping with corresponding reference genomes by using the HISAT2/ StringTie package. A total of 81,683 transcripts were generated against the coconut reference genome, while 9340 transcripts were generated against P. palmivora genome. Out of these, a total of 64,639 coconut transcripts and 9168 P. palmivora transcripts could be annotated using BLASTx. Gene ontology (GO) analysis, carried out using Blast2GO, resulted in 212,643 coconut and 30,736 P palmivora transcripts being functionally classified, with a single gene product described by numerous terms under the three classifications. The insights obtained could contribute to an understanding of pathogenesis of P. palmivora and inducible defense response of coconut leaves to P. palmivora.